Estimation of factors for standardizing lactation yield to mature equivalent and 305-day basis for Brown Swiss cattle reared at Ulas State Farm - Cileki, Soleyman; Emin Tekin, Mehmet (The Indian Journal of Animal Sciences, 2011)
In this study, adjustment factors oflactation milk yield to mature age and 305 days were estimated for Brown Swiss cattle from 3013 lactation records. Factors for adjusting the incomplete lactation to 305 days were calculated separately for 7 calving age groups, and the average of adjustment factors were also estimated for all the ages. For lactations less than 305 days, average of adjustment factors for 30th, 60th, 90th, I 20th, 150th, 180th, 21 Oth, 240th, 270th, 300th and 305th days, were 7.88, 4.0 1,2.66,2.04, 1.67, 1.43, 1.25, 1. I 6, 1.08, 1.0 I and 1.00 respectively. For lactations more than 305 days, the average of adjustment factors for 31 Oth, 340th, 370th, 400th, 430th, 460th, 490th, 520th, 550th, 580th and 600th days were 0.98, 0.93, 0.88, 0.84, 0.80, 0.76, 0.73,0.70,0.67,0.65 and 0.64 respectively. Adjustment factors for mature age were calculated by using polynomial regression. Adjustment factors were estimated as 1.13 and 1.20 for cows calving in 24th month and for cows calving in 143rd month, respectively, with mature age from 67 to 89 month.